Global business regulation - Braithwaite, John 1951-; Drahos, Peter 1955- (Cambridge University Press, 2020)
Across an amazing sweep of the critical areas of business regulation - from contract, intellectual property and corporations law, to trade, telecommunications, labour standards, drugs, food, transport and environment - this book confronts the question of how the regulation of business has shifted from national to global institutions. Based on interviews with 500 international leaders in business and government, this book examines the role played by global institutions such as the WTO, the OECD, IMF, Moody's and the World Bank, as well as various NGOs and significant individuals. The authors argue that effective and decent global regulation depends on the determination of individuals to engage with powerful agendas and decision-making bodies that would otherwise be dominated by concentrated economic interests. This book will become a standard reference for readers in business, law, politics and international relations